STUDI KASUS: DIABETES MELITUS DISERTAI KOMPLIKASI CHRONIC KIDNEY DISEASE (CKD) DAN STROKE NON HEMORAGIK - Wulansari, Esti; Novita Kumalasari, Dian (Journal Healthcare Education, 2023)
The number of patients suffering from Diabetes Mellitus in January - 2023 who were treated in Abimanyu Ward was 74 people. This research aims to obtain a picture and real experience in implementing nursing care for patients with Diabetes Mellitus accompanied by complications of Chronic Kidney Disease and Non-Hemorrhagic Stroke using the nursing process. This research method uses a descriptive method, while to complete the data it uses interviews, observation, physical examination and documentation studies. In providing nursing care, the author uses the nursing process which consists of assessment, nursing diagnosis, nursing planning, nursing implementation and evaluation. The research results showed that there were eight nursing problems that emerged. In theory, there are fifteen nursing diagnoses that appear in patients with Diabetes Mellitus, Chronic Kidney Disease (CKD) and Non- Hemorrhagic Stroke. Meanwhile, in the case, 3 diagnoses emerged that were in accordance with the theory, namely instability of blood glucose levels, risk of ineffective cerebral perfusion and risk of infection. And the diagnoses found in the case but not in theory were: noncompliance, hypervolemia, impaired tissue integrity, ineffective peripheral perfusion and disturbed sleep patterns. The conclusion of the research is that there are three nursing problems, the goals achieved are the risk of cerebral perfusion, while the goals partially achieved are instability of blood glucose levels and risk of infection.